A novel cold‐adapted pullulanase from Exiguobacterium sp. SH3: Production optimization, purification, and characterization. Issue 3 (23rd August 2013) - Rajaei, Sarah; Heidari, Reza; Shahbani Zahiri, Hossein; Sharifzadeh, Sara; Torktaz, Ibrahim; Akbari Noghabi, Kambiz
<x xml:space="preserve">Abstract</x> Cold‐adapted enzymes, elaborated by psychrophiles and psychrotrophs, seem to have potential for current and future applications. In the current study, pullulanase production by the cold‐adapted Exiguobacterium sp. SH3 was investigated. The Plackett–Burman design and the response surface methodology were applied to identify and optimize the significant variables affecting the pullulanase production of Exiguobacterium sp. SH3. The results showed that temperature, time, and CaCl2 concentration were significant variables while shaking, starch, yeast extract, tryptone, pH, MnCl2, MgCl2, and KH2PO4 were not significant. Using statistical analyses and optimizations, the pullulanase production was significantly elevated from 200 ± 18 to 950 ± 27 U/mL (4.75 times) as compared to non‐optimized conditions. A pullulanase of about 70 kDa, designated as Pul‐SH3, was purified 16.2‐folds from the optimized culture, and identified to be an amylopullulanase. The Km and Vmax of the enzyme were 0.069 mg/mL and 967 U/mL, respectively. The optimum pH and temperature for maximum activity of Pul‐SH3 were 7.5 and 30°C, respectively. As a cold‐adapted enzyme, Pul‐SH3 retained 23% of the maximum activity at 0°C. The biochemical characteristics and N‐terminal amino acid sequence of Pul‐SH3 suggest that the enzyme is a novel cold‐adapted amylopullulanase with remarkably high specific activity at moderate ambient temperature.